Penerapan Model Guided-Discovery Learning (GDL) dengan Pendekatan Saintifik Berbantuan Geogebra Pada Topik Geometri - Simamora, Rustam E; Siagian, Meryance V (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
This study aims to determine the effectiveness of the application of the Guided-discovery learning model with a scientific approach assisted by GeoGebra software and student attitudes in learning mathematics on the topic of Geometry. This type of research is applied research. The population of this study were high school students and the sample of this study were students of class XII. The results of this study indicate that: the application of the Guided-discovery learning model with the scientific approach assisted by GeoGebra software on the topic of Geometry will be effective in teaching students, the application of the Guided-discovery learning model with the scientific approach assisted by GeoGebra software on the topic of Geometry will make students positive in learning mathematics